Reasons for Conversion and Adverse Intraoperative Events in Robotically Enhanced Minimally Invasive Coronary Artery Revascularization. Issue 3 (May 2020) - van der Merwe, Johan; Casselman, Filip; Vermeulen, Yvette; Stockman, Bernard; Degrieck, Ivan; Van Praet, Frank
Objective: The transition from sternotomy access to minimally invasive coronary artery bypass grafting is associated with steep learning curves. This study reports the reasons for sternotomy conversions from robotically enhanced minimally invasive direct coronary artery bypass grafting (RE-MIDCAB) and describes potential risk reduction strategies. Methods: The perioperative data of 759 RE-MIDCAB patients (mean age 65.9 ± 10 years, 25.5% female, 30.2% multivessel disease) operated between July 1, 2002 and November 30, 2018 were reviewed for the reasons of conversion and adverse intraoperative events. Hybrid revascularization was planned in 204 (26.9%) patients. Results: Sternotomy conversion occurred in 30 (4.0%) patients. Lung adhesions and unsuccessful single-lung ventilation prohibited safe RE-MIDCAB internal thoracic artery (ITA) harvesting in 11 (36.7%) and 1 (3.3%) patients, respectively. ITA dysfunction ( n = 11, 36.7%) and inadequate target vessel visualization ( n = 3, 10.0%) were among the anatomical reasons for conversions. Adverse intraoperative events included ventricle perforation ( n = 1, 3.3%) and sustained ventricular arrhythmia ( n = 1, 3.3%). The in-hospital mortality and mean length of hospitalization for sternotomy conversion were 3.3% ( n = 1 of 30) and 13.4 ± 14.5 days, respectively. Perioperative morbidities included pneumonia ( n = 4, 13.3%). Premorbid renal dysfunction predicted sternotomy conversion at the 5% level of significance. Conclusions: RE-MIDCAB provides an attractive surgical platform for primary- or hybrid coronary artery procedures. The progressive increase in patient risk profiles, strict quality control, and focus on clinical governance require awareness of reasons that potentially contribute RE-MIDCAB to sternotomy conversion to ensure safe and sustainable programs.